Recommendations for the prevention, screening, diagnosis, staging, and management of cervical cancer in areas with limited resources: Report from the International Gynecological Cancer Society consensus meeting - Maluf, Fernando Cotait; Dal Molin, Graziela Zibetti; de Melo, Andreia Cristina; Paulino, Eduardo; Racy, Douglas; Ferrigno, Robson; Uson Junior, Pedro Luiz Serrano; Ribeiro, Reitan; Moretti, Renato; Sadalla, Jose Carlos; Nogueira-Rodrigues, Angelica; Carvalho, Filomena Marino; et al. (Frontiers in Oncology, 2022)
ABSTRACT Introduction: Nearly 85% of cervical cancer new cases are diagnosed in limited resources countries. Although several strategies have been proposed to reduce the disease burden, challenges remain to provide the best possible care. We report recommendations from an expert consensus meeting convened to address from prevention to management of cervical cancer in limited resources countries. Methods: The expert panel, composed by invited specialists from 38 developing countries in Africa, Asia, Eastern Europe, Latin America, and the Middle East, convened in Rio de Janeiro in September 2019, during the Global Meeting of the International Gynecological Cancer Society (IGCS). Panel members considered the published scientific evidence and their practical experience on the topics, as well as the perceived cost-effectiveness of, and access to, the available interventions. The focus of the recommendations was on geographic regions rather than entire countries because medical practice varies considerably in the countries represented. Resource limitation was qualified as limited access to qualified surgeons, contemporary imaging or radiation-oncology techniques, antineoplastic drugs, or overall funding for provision of state-of-the-art care. Consensus was defined as at least 75% of the voting members selecting a particular answer of the multiple-choice questionnaire, whereas the majority vote was considered as 50% to 74.9%. Results: Consensus was reached for 25 of the 121 (20.7%) questions, whereas for 54 (44.6%) questions there was one option garnering between 50% to 74.9% of votes (majority votes). For the remaining questions, considerable heterogeneity in responses was observed. Discussion: The implementation of international guidelines is challenging in countries with resource limitations or unique health-care landscapes. The development of guidelines by the health care providers in those regions is more reflective of the reality on the ground and may improve medical practice and patient care. However, challenges remain toward achieving that goal at political, economic, social, and medical levels.